Perceptions and Practices: A Survey of Professional Engineers and Architects. (28th March 2012) - Cunningham, Don; Stewart, Jill
Abstract : This descriptive cross-sectional research study examines perceptions of time spent by architects and professional engineers on reading, writing, and evaluating various information products, as well as their perspectives of specific quality characteristics and the relative significance in meeting work goals. Professional engineers and architects were surveyed at seminars held at eight locations in seven states. Descriptive statistics were then used to investigate perceptions and relationships. Findings indicate architects and professional engineers spend the most amount of time reading correspondence and the least amount of time reading management reports. Respondents considered correspondence to be the most important reading activity. Participants also spend the most amount of time writing correspondence, closely followed by nearly equal time spent writing and editing technical reports and proposals. Finally, participants rated organization, comprehensiveness, and accuracy as the most important aspects while indicating mechanical issues such as grammar and spelling as the least important aspects of technical documents.